Synthesis, spectroscopic and antimicrobial studies of Mn(II), Fe(II), Co(II), Ni(II), Cu(II) and Zn(II) complexes with N-aminoquinoline derivatives. - Hassan, I.A. (Al-Qadisiyah Journal of Pure Science, 2017)
Novel transition metal (II) complexes, [M(L1)2]Cl2 and [M(L2)2Cl2], were synthesized from the reaction of MCl2.nH2O (M =Mn, Fe, Co, Ni, Cu, Zn) with N-[N-(1,2-diphenyl)ethanol amino] cumarine (L1), N-[4-(Î±-methyl) pyrilidino] cumarine (L2). The ligands were obtained from cumarine. N-aminoquinoline-2-one has been synthesized by the reflux of cumarine with hydrazine hydrate in ethanol for 12 hrs. the azomethanes (L1, L2) were prepared from the corresponding benzoin and 4-acetylpyridine. The synthesized compounds were characterized by microanalysis (M), molar conductance, magnetic measurement, infrared and electronic spectra . The IR spectral data suggest the involvement of carbonyl, hydroxyl and azo methane nitrogen in coordination to the central metal ion. On the bases of the spectral studies an octahedral geometry has been for all complexes .The free ligands and its metal complexes have been tested in vitro against number of microorganisms in order to assess their antimicrobial properties.